The modern trends of the foreign trade policy implementation: implications for customs regulations - Kormych, Borys; Кормич, Б. А. (Одеса : Гельветика, 2018)
The paper analyses basic transformation tendencies in the international trade policy standards generated within frameworks of global and regional institution and their influence upon customs and border formalities. The transformation of standards is also supplemented with crucial changes in a rule-making process, that conventionally has been an exclusive competence of national states. That rule-making changes are charac-terised by transferring the significant amount of competence from the national states to the global and supranational level, as well as by introduction new types of rule-making actors (both public and private) and new types of law sources. This urges us to apply to the analyses the concepts of global governance, transnational law and global administrative law, which focus on the above-mentioned transformations in the field. Customs authorities now are experiencing the transition of their initial mission from merely revenue collectors to actors responsible for extensive range of tasks, including safety and security issues, trade facilitation, joint border management, etc. All these tasks should be performed at the high level of harmonisation, unification and standardization with recognised international and regional rules and regulations. Due to the specifics of the new mission of customs authorities, the paper primary focuses on two relatively new tasks of security and trade facilitation. And also paper discuses two basic modern instruments to implement such tasks – the operation of Single Window for international trade and the application of good governance principles to customs routine opera tions. The essential point is that two instruments are not focused merely on improving the way customs and border formalities are performed by authorities, but also starve the whole system of border management into comprehensive reform of both interagency and intra-agency procedures and operations. The Single Window facility provides such reform through joint application of information technology based on internationally approved standards. The WTO rules for good governance for application of customs legislation in fact demands from member states to share common values and principles, originally emerged within legal systems of western developed countries. У роботі аналізуються основні тенденції трансформації стандартів між- народної торговельної політики, сформованих у рамках глобальних та регі- ональних інституцій, та їх вплив на митні та прикордонні формальності. Трансформація стандартів також доповнюється важливими змінами у процесі нормотворення, що традиційно було винятковою компетенцією національних держав. Відповідні зміни характеризуються переходом значного обсягу компетенції від національних держав на глобальний і наднаціональний рівень, а також появою нових типів акторів, що здійснюють нормотворчість (як державних, так і приватних) та нових типів джерел права. Це спонукає нас звернутися до аналізу концепцій глобального управління, транснаціонального права та глобального адміністративного права, які сфокусовані на вищезгаданих трансформаціях у цій галузі. Митні органи зараз переживають перехід від традиційної місії лише збирачів податків до суб’єктів, відповідальних за широкий спектр завдань, включаючи питання безпеки та захисту, сприяння торгівлі, спільного управління кордонами тощо. Всі ці завдання повинні виконуватися на високому рівні гармонізації, уніфікації та стандартизації з визнаними міжнародними та регіональними нормами та правилами. З огляду на специфіку нової місії митних органів, основна увага приділяється їх двом відносно новим завданням: забезпечення безпеки та спрощення процедур торгівлі. Відзначено також основні сучасні інструменти для реалізації таких завдань: функціонування “єдиних вікон” для міжнародної торгівлі та застосування принципів належного урядування до митних операцій.
The modern trends of the foreign trade policy implementation: implications for customs regulations
Kormych B. The modern trends of the foreign trade policy implementation: implications for customs regulations / B. Kormych // Lex Portus : юрид. наук. журн. / редкол. : С. В. Ківалов (голов. ред. ради), Б. А. Кормич (голов. ред.), І. В. Сафін (заст. голов. ред.), Т. В. Аверочкіна (наук. ред., відп. секр.) [та ін.] ; НУ "ОЮА", ГО "МА Святий Миколай". - Одеса : Видавничий дім «Гельветика», 2018. - № 5. – C. 27 - 45.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; торговельна політика; митні правила; митні формальності; сприяння торгівлі; “єдине вікно”; СОТ; ВМО; СЕФАКТ ООН; торговая политика; таможенные правила; таможенные фор- мальности; содействие торговле; ВТО; СТС; trade policy; customs regulations; customs formalities; trade facilitation; Single Window; WTO; WCO; UN/SEFACT Introduction